Public engagement throughout the research process in a health and socio-demographic surveillance system study area in rural South Africa - Twine, Rhian (My University, 2019)
Background Research governance in longitudinal health research areas, particularly with vulnerable populations, requires effective public engagement. The overall aim of this thesis is to explore and extend understandings of public engagement in a longitudinal health and demographic surveillance system study area (HDSS) in rural South Africa. The four research papers deal with public engagement throughout the research process: public involvement in research governance including the co-production of knowledge in research protocol development; dilemmas of ethics in practice or ethics in the field; mechanisms for knowledge transfer and translation of research findings to the experimental public; and the views of the experimental public on living within a longitudinal HDSS study area. Methods The case study derives from a longitudinal health study area in rural South Africa: the Medical Research Council / Wits University Rural Public Health and Health Transitions Research Unit (Agincourt). This is a mixed methods case study of public engagement throughout the research process. The qualitative mixed methods used were: a modified Delphi exercise; participatory visualisation; ethnographic field notes; individual, natural and focus group interviews with residents, village leaders, and service providers; and responses to critical incident scenarios from researchers who had been involved in nested research projects. Quantitative data were from secondary analysis of reports on village-based dissemination of findings. Findings Public engagement is increasingly regarded as an essential component in public health research and research governance. This thesis has extended knowledge on the lived experiences of experimental publics, namely residents in longitudinal health research areas. Firstly, public engagement and involvement in protocol development has the potential to shape research priorities and budgets. Secondly, there is an understanding and acceptance of being part of public health research, but there were concerns about some ethics in practice issues. These included requests for increased researcher accountability in relation to giving back individual screening results and more effective and targeted dissemination of results. Thirdly public engagement as part of research governance in longitudinal public health research areas has the potential to enhance mutual trust, ethics in practice and science as a public good. Conclusion The case study is an original contribution to knowledge on the dynamics, mechanisms and meanings of public engagement in longitudinal public health research, and its importance for ensuring fair benefit for research participants. These research findings on public engagement within the HDSS are generalisable, and relevant in relation to research governance in longitudinal health research areas. A synthesis of models of public engagement and knowledge brokerage were developed into a hub and spokes model of public engagement that could guide longitudinal research organisations to improve public engagement at all stages of the research process. The focus on ethics in practice with an experimental public as part of civic science provides a framework for analysis of public engagement and research governance within public health longitudinal research areas.
Original published work submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of PhD in Public Health Johannesburg, June 2019